Analysis of Factors Affecting Consumers in UHT Milk Consumption: The Case Study of Erzurum - Ahmet Semih Uzundumlu; Avni Birinci; Seval Kurtoğlu (Turkish Journal of Agriculture: Food Science and Technology)
The primary purpose of this study was to determine factors influencing consumer preferences for UHT milk consumption in Erzurum province. The primary data used in this research was derived from Palandoken, Yakutiye and Aziziye districts of Erzurum province in 2010. The factor analysis was used to find out the factors affecting consumer preferences for UHT milk and to reduce these factors. As for the segmentation of consumers and bringing out the profile of each segment, cluster analysis was used. According to the results, 95.00% of households consumed UHT milk. 18 factors that are affecting the consumption of UHT milk were reduced to five main factors with factor analysis. The factor scores which determined with factor analysis were divided into three clusters by cluster analysis. UHT milk for consumers entering the first cluster has because of homogenous and packaging as well as intrinsic and extrinsic properties for advertising and price advantage is preferred. UHT milk for consumers entering the second cluster has ease of preparation and transportation, and confidential properties are preferred by reason. On the contrary, consumers entering the third cluster prefer to UHT milk for a good diet product.